Implementation of Finding Shortest Route for Pharmacy Location Using A-star Algorithm - Juniawan, Fransiskus Panca; Sylfania, Dwi Yuny; Agrina, Dini (JOIN (Jurnal Online Informatika), 2019)
The number of pharmacies in the Pangkalpinang City has increased rapidly. This is directly proportional to the needs of the people of Pangkalpinang City to fulfill the health needs, buy medicine or divert doctor's prescriptions. This is a debate for people who do not know the location of pharmacies in this city. Practically, people can just go to a pharmacy with a location that far from user location, even though there is a pharmacy near the user. This is because there is no pharmacy information location in the Pangkalpinang City. To solve this problem, proposed a system that can display the location of all pharmacies in the Pangkalpinang City. In addition, the system can search the shortest path from the user's location to the nearest pharmacy location around using the A * algorithm. This algorithm was chosen because its advantages that are able to produce optimal solutions according to the expected heuristic functions. The results of the testing are that the system can optimize and be able to search the shortest path from the user's location to the nearest pharmacy.